Деревні рослини в озелененні населених пунктів східного району південного берега Криму - Potapenko, I.L.; Kuznetsov, S.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
This paper provides the data about taxonomy, flora and age of the arboreal plants cultivated in the populated areas of the eastern region of the Crimean coast. Plants that are used in this area consist of 170 species, 8 hybrids and 24 decorative forms of wooden plants. The majority of species represented in this area belong to Mediterranean flora (42 species or 24.7%). Analysis of the living forms was conducted and showed that the leading part belonged to the leaf-bearing foliage trees (78 species or 38.6%). The richest diversity of tree and shrub species and forms were noted in Koktebel estate – 114 species, hybrids and cultivated plants (31.7% of the total number). In all, the assortment of the decorative arboreal plants is small and needs to be expanded.